The Effects of Ice on Coal Movement via the Inland Waterways. - Lunardini,Virgil J , Jr; Minsk,L David; Phetteplace,Gary E (1981)
The Inland Waterways now carry about 11% of the coal production of the United States. Significant increases in the production, use, and transportation of coal have been projected. The ability of the Inland Waterways to increase its coal handling capacity, especially during the winter has been questioned. That part of the Inland Waterways which carries significant coal and which may experience significant ice problems includes the following rivers or waterways: Ohio, Monongahela, Allegheny, Kanawha, Upper Mississippi, and Illinois. Coal transportation along these rivers may be locally interrupted for periods up to 30 days or more every three to five years. Coal handling facilities, navigation channels, and lock and dam sites along the ice prone rivers were surveyed by visit or telephone to ascertain the scope of the ice problems. Coal moves through any part of the waterways system as a series flow from the coal loading/unloading facilities, along the navigation channels and through the locks to its destination. The importance of ice as a barrier to increased coal movement on the waterways studied manifests itself differently for each link of the flow system. In order of importance the ice will affect the navigation channels, locks and dams, and finally the coal loading/unloading facilities. The coal handling facilities will not be significantly slowed down by ice problems associated with winter navigation. Only rarely is a coal handling facility stopped by ice when the locks and dams or navigation channels are operating normally. The major exception may be the rail car to barge loading link which can cause slowdowns due to coal freezing in the rail cars. (Author)